AUGMENTED MARKETING COMMUNICATIONS: AR-BASED MARKETING IN THE BANKING WORLD - Tito Wira Eka Suryawijaya; Zora Calista Susilo; Masitha Fahmi Wardhani (Jurnal Telekomunikasi dan Informatika, 2023)
In line with technological developments that continue to advance, companies need to continue to adapt in order to survive. Permata Bank as part of the banking industry must also adapt to establish communication in the digital realm with its consumers by carrying out product branding and marketing. Permata Bank's Choice of Augmented Reality is a mini game in the form of an Instagram filter. The purpose of this research is to see the effectiveness of AR mini games which play a role in increasing awareness of Permata Bank banking products or services to increase customer interest, engagement, and loyalty. This study uses the SEM-PLS method. The data was obtained through observation and online studies with customers to find out the activities of respondents with Augmented Reality by distributing online questionnaires with a sample of 100 respondents to find out the relationship between user experience, customer satisfaction, customer involvement and customer loyalty. This research uncovers the development of marketing techniques, which incorporate Augmented Reality (AR) technology to enhance consumer experience and increase their interaction with products or services. These techniques have an impact on increasing brand awareness, product understanding, and customer engagement with services. Through the use of AR technology, new marketing techniques have been discovered. Augmented Marketing Communications. The limitations of this study are limited to marketing communications in the banking sector. There has been a lot of research done to discuss augmented reality. However, there is not much research that addresses the banking sector specifically.